Level penalaran aljabar siswa dalam menyelesaikan soal model PISA ditinjau dari gaya kognitif Witkin - Nursirot, Mohammad Arul Sholehuddin; Ulfa Masamah; Abdussakir (Pusat Studi Pengembangan Pembelajaran Matematika, 2025)
Algebraic reasoning is the process of generalizing mathematical ideas through logical reasoning, involving patterns, variable relationships, and the analysis of abstract structures to construct valid mathematical arguments. This qualitative research aims to examine the levels of students' algebraic reasoning in solving PISA model problems in terms of Witkin's cognitive styles. The research subjects were six eighth-grade students from MTsN Kota Batu. Data were collected through written tests, think-aloud protocols, task-based interviews, and documentation. Data analysis was conducted using the constant comparative method, encompassing the stages of reduction, categorization, synthesis, and the development of substantive theory. The results showed that students with a field-dependent cognitive style could identify patterns and regularities but struggled to design variables and formulate equations as part of the generalization process, resulting in their algebraic reasoning being classified at level 1. In contrast, students with a field-independent cognitive style were able to perform mathematical symbolization, generalize, and formulate equations, but were inconsistent in defining variables and did not utilize the derived formulas to solve problems, placing their algebraic reasoning at level 2. These findings indicate that differences in students' cognitive styles influence their abilities to comprehend, formulate, and apply algebraic reasoning concepts, including selecting appropriate problem-solving strategies and maintaining consistency in mathematical generalizations.